两种硅藻的光合生理研究 - 阎冬 (2018)
在海洋环境中，时间、水深以及悬浮物等都会影响阳光辐射。浮游植物所接受的光强除了与以上因素之外还会受到海水混合的影响。因此，认知光强变化与浮游植物生理过程的关系对解析海洋初级生产过程的变化尤为重要。近岸水域受潮汐等的影响，浮游植物处于较大、较频的光变环境中；在海冰区，春季水温升高海冰融化，冰藻群落通常会暴露于较高的光强下。本论文选取了两种硅藻，中心硅藻纲的格氏圆筛藻(Coscinodiscusgranii，分离自厦门市五缘湾)和羽纹硅藻纲的一种菱形藻(Nitzschiasp.，分离自北海道Saroma湖)，开展了其光合生理的研究。 将格氏圆筛藻细胞在70，125，225，450μmolphot. The underwater light climate changes with time and water depth. It is also closely related to suspended matters in the water column. In order to better estimate the primary productivity in the ocean, it is of great importance to understand the photophysiological responses of phytoplankton to changing light. Phytoplankton in coastal waters experiences large fluctuations with variations of light. Ic. 学位：理学硕士 院系专业：海洋与地球学院_海洋生物学 学号：22320141151365